Brain targeted delivery of paclitaxel using endogenous ligand - Sanjeev R. Acharya; Padmanabha R.V. Reddy (Elsevier, 2016)
The objective of the present investigation was to formulate nanoparticles constructed using PLGA polymer for the effective targeted delivery to brain via nasal route. The PLGA nanoparticles were optimized using novel design of experiment technique by 23 full factorial design. Drug: polymer ratio (X1), surfactant concentration (X2) and stirring speed (X3) were identified as critical process parameters, and its impact on particle size (Y1) and % entrapment efficiency (Y2) was studied. The optimized nanoparticle formulation was conjugated with glutathione as an endogenous ligand by using carbodiimide chemistry using (1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide) (EDAC) as linker molecule. From Ellman's assay, it was found that a total of 691.27 ± 151 units of glutathione were conjugated upon each PLGA nanoparticle. The in vitro release studies as well as ex vivo studies revealed biphasic pattern of drug release with initial burst release followed by slow exponential release of drug over a period of 24 h. The in vivo biodistribution studies were conducted on rat following nasal administration of the nanoparticle formulation (conjugated and unconjugated) and were compared with plain paclitaxel suspension. The results clearly demonstrated that the brain targeting efficiency was enhanced with the glutathione conjugated formulation (387.474%) as compared to the unconjugated nanoparticle formulation (224.327%). Further, the in vitro in vivo correlation studies revealed good relationship (R2 > 0.95) as obtained from the levy plot. Glutathione proves to be an efficient vector for the successful transport of poor bioavailable drug to the brain.